Contribution of unparticles to the Møller scattering in the Randall-Sundrum model - Dang, Van Soa; Le, Mai Dung; Thủy, Đào Thị Lệ (Communications in Physics, 2023)
The influence of vector, scalar unparticle exchange and photon \((γ)\), \(Z\) boson, Higgs-radion \((h,φ)\) exchange on the fundamental Møller scattering in Randall-Sundrum model is presented. We evaluated the contribution from each exchange in standard model physics and unparticle physics to the final production cross-sections with the apposite energy reach in the current accelerators and colliders. The results indicate that the effect of vector unparticles is larger than its scalar all over the range of collision energy, as much greater than Higgs \((h)\) and radion \((φ)\) in the low energy. \(Z\) boson exchange also contributes the greatest to the process in both unpolarized and polarized conditions in higher energy regions when compared to photon exchange \((γ)\) which normally dominates at the lower energies.